Análise não-linear de estruturas reticuladas espaciais de concreto armado - Martins, Paulo Chaves de Rezende (1979)
Present an automatic program for non-linear analysis of spacial frames of reinforced concrete, including verification of structures under definite loading and research on its load-bearing capacity for a given disposition of loads. On its development are considered both the non-linearity of the stress-strain diagrams of the materials (physical non-linearity) and the second order effects of the axialflexural interaction (geometrical non-linearity). ln the case of structure loaded by torsion, combined or not with others efforts, the effects of torsion are considered on an approximative way, based on the spacial truss model, adopted by the C.E.B. The final part presents some examples of application of the automatic program and some comparisons with others methods of analysis and experimental investigations. Some comments about the results obtained and suggestions for more advanced studies in the future are also included.